2000
DOI: 10.1095/biolreprod63.5.1531
|View full text |Cite
|
Sign up to set email alerts
|

Seminal Plasma Proteins Revert the Cold-Shock Damage on Ram Sperm Membrane1

Abstract: Ejaculated ram spermatozoa, freed from seminal plasma by a dextran/swim-up procedure and exposed to cold shock, were incubated with ram seminal plasma proteins and analyzed by fluorescence markers and scanning electron microscopy. Seminal plasma proteins bound to the sperm plasma membrane modified the functional characteristics of damaged spermatozoa, reproducing those of live cells. Scanning electron microscopy showed that the dramatic structural damage induced by cooling reverted after incubation with semina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
112
3
21

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(158 citation statements)
references
References 49 publications
9
112
3
21
Order By: Relevance
“…Furthermore, proteins from DRMs and non-DRMs are lost after capacitation and the acrosome reaction. These results are consistent with previous reports that describe the release of sperm membrane proteins during capacitation of bull [70], boar [71,72], rabbit [73] or ram [74] spermatozoa.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, proteins from DRMs and non-DRMs are lost after capacitation and the acrosome reaction. These results are consistent with previous reports that describe the release of sperm membrane proteins during capacitation of bull [70], boar [71,72], rabbit [73] or ram [74] spermatozoa.…”
Section: Discussionsupporting
confidence: 94%
“…Previously, we demonstrated that the adsorption of seminal plasma proteins on ram sperm plasma membranes could partially prevent and repair cold-shock sperm membrane damage (Pérez-Pé et al, 2001a,b), and that this adsorption modified the functional characteristics of damaged spermatozoa reproducing those of live cells (Barrios et al, 2000;Pérez-Pé et al, 2001a). More recently (Barrios et al, 2005), we have proven that 2 proteins of approximately 14 (P14) and 20 (P20) kDa are responsible for this protective and restoring effect.…”
Section: Discussionmentioning
confidence: 95%
“…Polyclonal antibodies were raised against the whole seminal plasma fraction 6 (F6) isolated by exclusion chromatography in Sephacryl-100 (Barrios et al, 2000), and the purified P14 and P20 bands were recovered by electroelution from a nondenaturing gel (Barrios et al, 2000) by rabbit immunization with 500 mg (F6) and 300 mg (P14 and P20) of protein in Freunds complete adjuvant. After 15 days they were reimmunized with the same amount dissolved in Freunds incomplete adjuvant.…”
Section: Polyclonal Antibodiesmentioning
confidence: 99%
“…Asimismo se ha demostrado que el PS completo en exceso tiene un efecto nocivo para la viabilidad espermática (22). Por su parte, Barrios et al (1), describió, en ovinos, que la adición del conjunto de proteínas de PS, aunque no disminuye la viabilidad después de someter los spz a choque térmico por frío, tiene un efecto de recuperación de la viabilidad menor que el ejercido por la adición de la fracción 6 (con proteínas de 14 y 20 kDa), y que la adición de fracciones de PS, que contienen proteínas con pesos moleculares superiores a 60 kDa, no tiene mayor efecto en la recuperación de la viabilidad del semen ovino.…”
Section: Discussionunclassified
“…Estas proteínas, son secretadas por las vesículas seminales (11)(12)(13), y se han empleado para proteger al spz contra el estrés térmico y oxidativo (14,15). Igualmente, se ha demostrado que la incubación de spz in vitro con proteínas de PS, puede contrarrestar los daños ocasionados a las células espermáticas sometidas a choques térmicos (1,13).…”
Section: Introduccionunclassified